Penyuluhan Manfaat Dan Keamanan Vaksin Covid-19 Di SMPIT Almadinah, Cibinong, Bogor - Isa Bella; Jihan Samira Thabit; Noviani Prasetyaningsih; T Robertus; Monica Dwi Hartanti (AMMA : Jurnal Pengabdian Masyarakat, 2023)
SMPIT Almadinah is a private educational institution with 426 students, located on Jl. Sukahati No.36, Karadenan, Cibinong, Bogor, West Java 16913. In August 2021 the SMPIT Almadinah school in collaboration with the government held a Covid-19 vaccination for teachers and students in preparation for the start of offline learning. Some students missed the event due to a concern of benefits and safety of the Covid-19 vaccine. The purpose of this activity was to increase the understanding of SMPIT Almadinah Cibinong students about the importance of the Covid-19 vaccine and the safety of the Covid-19 vaccine. Counseling of the knowledge about SarsCov2 virus, the Covid-19 vaccine, and the human immune response was expected to increase the knowledge of SMPIT Almadinah students. When knowledge about the importance of the Covid-19 vaccine is better, it is hoped that it will be easier to accept recommendations to be willing to accept the Covid-19 vaccine. The indicator of the increase in knowledge about the SarsCov2 virus and the Covid-19 vaccine can be assessed by providing questionnaires at pre-counseling and post-counseling. The implementation of this outreach activity conducted online. This activity was preceded by a field survey and interviews with the school regarding the needs that could be facilitated by this activity. In conclusion, this activity was appreciated by students of SMPIT Almadinal school and future activities related to this topic should be conducted continously.